Pine Forest Tourism Destination Business Development Strategy Malino, Tinggi Moncong District Gowa Regency - Ridhawati, Ridhawati; Aslinda, Aslinda; Saleh, Sirajuddin; Kasmita, Maya (Jurnal Administrasi Bisnis, 2025)
This study aims to determine the business development strategy for the Malino pine forest tourism, Tinggimoncong District, Gowa Regency. The research method used is a qualitative method with data collection techniques, namely observation, interviews and documentation, and analyzed using SWOT analysis techniques. This research was conducted at the Department of Tourism and Culture, Gowa Regency. The instrument used in this study was the researcher himself (Human Instrument). Checking the validity of the data used to determine the level of confidence in the research results, namelyTriangulation andMemberCheck. From the results of the SWOT analysis, the main strategy used by the Gowa Regency Tourism and Culture Office is the strategy as a plan. As for the implementation of the identified development strategy, namely the aspect of Attraction, it is still being developed. in terms of transportation, tourist information centers, money processors, theaters, as well as several roads that still need to be repaired so that tourists visiting the Malino pine forest tour feel comfortable. This means that the strategy used by the Gowa Regency Tourism Office in business development for the Malino pine forest tourist destination is to first carry out planning starting from the management system, developing human resources, facilities and infrastructure planned from the start. For further development, cooperate with the marketing sector to carry out promotions.   Keywords:Strategy, Business Development.